Mutant prevention concentrations of ciprofloxacin against urinary isolates of Escherichia coli and Klebsiella pneumoniae - Ziad Daoud; Elie Salem Sokhn; Eid Azar; Khalil Masri; Shira Doron (Journal of Infection in Developing Countries)
Introduction: The aim of this work was to study the ability of ciprofloxacin to restrict the development of resistant mutants of Escherichia coli and Klebsiella pneumoniae through determination of the Mutant Prevention Concentration (MPC). Methodology: We studied 140 strains of E. coli and 86 strains of K. pneumoniae with different profiles of sensitivity to fluoroquinolones and extended spectrum beta lactamase (ESBL) production. The MPCs were determined using an inoculum of 1010 CFU/ml in Mueller-Hinton agar plates with serial concentrations of ciprofloxacin. Results: Ciprofloxacin-susceptible ESBL-producing strains showed a higher MPC for ciprofloxacin (P <0.001) than ciprofloxacin-susceptible non ESBL-producing strains, while ciprofloxacin-resistant ESBL-producing and non ESBL-producing strains did not significantly differ. The presence of qnr variants was associated with elevated MPCs. This was observed for both tested organisms. Conclusions: Our study helps to explain the frequent finding of resistance to fluoroquinolones in ESBL-producing strains. Consequently, the use of concentrations of ciprofloxacin higher than the MIC in order to prevent the recovery and growth of resistant mutants is recommended.